Scenario Planning of Oil Offshore Support Vessel at PT Patria Maritime Lines - Afif, Fuad; Titus, Amol (The Indonesian Journal of Business Administration, 2015)
Abstract -This study describes the application of scenario planning analysis at PT Patria Maritime Lines were established on August 8, 2008. At first time the company was created to support the coal cargo group PT United Tractors Tbk. After having enough operational knowledge coal ship, PT Patria Maritime Lines try carry out cargo outside of the group itself. At the end of 2013, world coal prices tend to drop dramatically until today. To anticipate this case, the management of PT Patria Maritime Lines are challenged to diversify products to the oil offshore support vessels. The technique used in this method is to collect data and information related to oil offshore support vessels either directly or indirectly. The results of this method can be used in the decision-making process with regard to early warning, implications, and the options available in each scenario are compiled from the results of the internal and external analysis. There are four scenarios resulted from this method in the form of narrative as the largest possible picture and a recommendation for the company which later can be used as a reference in defining and developing the company's business strategy. These four scenarios are slow expansion, the consortium, stay tune, and aggressive expansion. Slow expansion scenario is a scenario where the PML will build the ship started from beginning at the shipyard with the aim of following the development of large competitors who are also doing the same thing. Consortium is a scenario where PML cooperation with other ship company to advance the bidding process. Scenario stay tune is a scenario where PML optimize the units that now exist. And the lattes is the scenario of aggressive expansion where PML invests massively better to buy ready stock of fleets and build fleet from beginning from the shipyard.Keywords: Oil Offshore Support Vessel, Strategic Decision Making, Scenario Planning